2022
DOI: 10.3390/polym14132645
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nanocoated Filaments for 3D Fused Deposition Modeling of Antibacterial and Antioxidant Materials

Abstract: Three-dimensional (3D) printing is one of the most futuristic manufacturing technologies, allowing on-demand manufacturing of products with highly complex geometries and tunable material properties. Among the different 3D-printing technologies, fused deposition modeling (FDM) is the most popular one due to its affordability, adaptability, and pertinency in many areas, including the biomedical field. Yet, only limited amounts of materials are commercially available for FDM, which hampers their application poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Nevertheless, most of the semi-crystalline polymers, including PBS, are underutilized for FDM due to the printing complications associated with their low melt strength and high warpage potential [25,26]. Our studies also showed that in addition to explicitly controlling the printing temperature and printing speed in a narrow range, melt stabilizing agents, such as lignin, must be added to print PBS with high quality and precision [20]. This could be why amorphous polymer-based filaments such as PLA and acrylonitrile butadiene styrene (ABS) are more commonly used for FDM printing, which is more flexible with selection of printing parameters (e.g.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, most of the semi-crystalline polymers, including PBS, are underutilized for FDM due to the printing complications associated with their low melt strength and high warpage potential [25,26]. Our studies also showed that in addition to explicitly controlling the printing temperature and printing speed in a narrow range, melt stabilizing agents, such as lignin, must be added to print PBS with high quality and precision [20]. This could be why amorphous polymer-based filaments such as PLA and acrylonitrile butadiene styrene (ABS) are more commonly used for FDM printing, which is more flexible with selection of printing parameters (e.g.…”
Section: Introductionmentioning
confidence: 72%
“…Previously, we developed polybutylene succinate (PBS)-based composite filaments incorporating lignin and assessed their printability in FDM [20]. Compared to other commercially available bioplastics, such as polylactic acid (PLA), PBS exhibits lower processing temperature, higher compliance, and better crystallinity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM), widely recognized as 3D printing, is an advanced technology to fabricate end-use items with innumerous complex geometric shapes according to computer-aided design. This disruptive technique is regarded as one of nine pillars of the fourth industrial revolution (Industry 4.0) owing to its automated production nature and mass-customized and on-demand manufacturing capacity. ,, In the past decade, numerous prodigious advances have been made in AM, including the emergence of 4D printing. , The concept of 4D printing was first initiated by Skylar Tibbits in 2013 by considering “time” as the fourth dimension . It is a revolutionary version of 3D printing, in which the size, shape, dimension, and physiochemical properties of printed structures can be dynamically programmed with the aid of various stimuli, such as pH, temperature, electricity, and magnet. , 4D printing is a space-age technique that has incredible potential in numerous applications, particularly where dynamic adaptation is required, e.g., soft robotics, aerospace, and biomedical application .…”
Section: Introductionmentioning
confidence: 99%
“… 1 3 This disruptive technique is regarded as one of nine pillars of the fourth industrial revolution (Industry 4.0) owing to its automated production nature and mass-customized and on-demand manufacturing capacity. 1 , 4 , 5 In the past decade, numerous prodigious advances have been made in AM, including the emergence of 4D printing. 1 , 6 The concept of 4D printing was first initiated by Skylar Tibbits in 2013 by considering “time” as the fourth dimension.…”
Section: Introductionmentioning
confidence: 99%
“…of melt filament [9] and print time, and also how feasible is the process, to be carried out in a controlled (closed) environment [10,11]. In some cases, pre-processing also involves changing the composition or micro-structure of the filament material to produce components with better surface finish, mechanical properties, and industrial application [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%